Analisis Keseimbangan Lintasan Proses Produksi Roti Manis Kasur Kombinasi di PT. Indoroti Prima Cemerlang - Putri, Ni Luh Ayu Uparina Yanti; Satriawan, I Ketut; Sadyasmara, Cokorda Anom Bayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 4 (2020): Desember, 2020)
PT Indoroti Prima Cemerlang is one of the Food  industries which produces bread with a brand Mr. Bread. the company had problems with the balance of the production line, so that it cannot meet consumer demand, this causing the company to not able meet the production targets. The purpose of this study is to calculate the increase in line balancing and decrease in idle time and determine the optimum number of work stations in the production process of product sweetbread combination at PT. Indoroti Prima Cemerlang. The method used in this study was the Ranked Position Weight (RPW) method with the results obtained that the number of work stations is reduced to 5 work stations, the line efficiency increases to 40% and balance delay decreased to 60% with idle time reduced to 29.019 seconds. Keywords : Line balancing, work station, idle time, balance delay, Ranked Position Weight